Immunisation with purified Coxiella burnetii phase I lipopolysaccharide confers partial protection in mice independently of co-administered adenovirus vectored vaccines. Issue 19 (5th May 2023) - Dold, Christina; Zhu, Henderson; Silva-Reyes, Laura; Blackwell, Luke; Linder, Aline; Bewley, Kevin; Godwin, Kerry; Fotheringham, Susan; Charlton, Sue; Kim, Young Chan; Pollard, Andrew J.; Rollier, Christine S.
Highlights: Adenoviral vectored vaccine constructs against Q fever were synthesised. Vaccine constructs elicited robust antigen-specific T cell immunity in mice. Comparable T cell immunity when co-administering several vaccine constructs. Formulating constructs with LPS or LPS alone gave protection against challenge. Abstract: Q fever is a highly infectious zoonosis caused by the Gram-negative bacterium Coxiella burnetii. The worldwide distribution of Q fever suggests a need for vaccines that are more efficacious, affordable, and does not induce severe adverse reactions in vaccine recipients with pre-existing immunity against Q fever. Potential Q fever vaccine antigens include lipopolysaccharide (LPS) and several C. burnetii surface proteins. Antibodies elicited by purified C. burnetii lipopolysaccharide (LPS) correlate with protection against Q fever, while antigens encoded by adenoviral vectored vaccines can induce cellular immune responses which aid clearing of intracellular pathogens. In the present study, the immunogenicity and the protection induced by adenoviral vectored constructs formulated with the addition of LPS were assessed. Multiple vaccine constructs encoding single or fusion antigens from C. burnetii were synthesised. The adenoviral vectored vaccine constructs alone elicited strong cellular immunity, but this response was not correlative with protection in mice. However, vaccination with LPS was significantly associated with lower weight loss post-bacterial challenge independent of co-administration with adenoviral vaccine constructs, supporting further vaccine development based on LPS.